Development of Chitosan-Based Antibacterial Bioplastic from Shrimp Shell Waste with the Addition of Patchouli Oil (Pogostemon cablin Benth) - Pardi, Pardi; K, M. Rizal; Mizar, Khalid; Rizki, Mentarina; Alex Aji Kusuma (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: Plastic waste pollution remains a critical global issue, with fossil-based plastics contributing significantly to environmental damage. Bioplastics derived from organic residues are a promising alternative for sustainable packaging. In this study, shrimp shell waste was converted into chitosan and combined with patchouli essential oil (PEO) and cellulose nanocrystals (CNC) from corn cob waste to develop antibacterial bioplastic films. PEO was incorporated using both Tween-80 and CNC-stabilized Pickering emulsions at different oil concentrations (20%, 30%, and 40%). The fabricated films were characterized for thickness, tensile strength, elongation, water solubility, moisture content, biodegradability, antibacterial activity, and morphology. Results showed that Tween-80 stabilized films exhibited the highest tensile strength (6.32 MPa), whereas CNC-based Pickering emulsions improved flexibility and antibacterial properties. Increasing PEO content in Pickering emulsions enhanced antibacterial activity against Staphylococcus aureus and Escherichia coli, with the C2E40 film achieving the largest inhibition zones (22.00 mm and 17.92 mm, respectively). Films containing CNC also displayed reduced moisture content and improved biodegradability, with up to 74.03% degradation in soil burial tests. SEM analysis confirmed more porous structures with increasing PEO concentration, particularly in Pickering emulsion films. Overall, CNC-stabilized emulsions effectively enhanced the incorporation and release of PEO, producing bioplastic films with improved antibacterial properties and biodegradability for potential food packaging applications. Abstrak: Pencemaran limbah plastik masih menjadi isu global yang krusial, di mana plastik berbasis fosil memberikan kontribusi besar terhadap kerusakan lingkungan. Bioplastik yang berasal dari residu organik menjadi salah satu alternatif berkelanjutan untuk kemasan ramah lingkungan. Pada penelitian ini, limbah cangkang udang diolah menjadi kitosan dan dikombinasikan dengan minyak nilam (patchouli essential oil/PEO) serta nanokristal selulosa (CNC) dari limbah tongkol jagung untuk menghasilkan film bioplastik antibakteri. PEO diinkorporasikan menggunakan dua metode, yaitu emulsi dengan Tween-80 dan emulsi Pickering yang distabilkan oleh CNC pada berbagai konsentrasi minyak (20%, 30%, dan 40%). Film yang dihasilkan dikarakterisasi berdasarkan ketebalan, kekuatan tarik, elongasi, kelarutan air, kadar air, biodegradabilitas, aktivitas antibakteri, dan morfologi. Hasil menunjukkan bahwa film dengan emulsi Tween-80 memiliki kekuatan tarik tertinggi (6,32 MPa), sedangkan emulsi Pickering berbasis CNC meningkatkan fleksibilitas dan aktivitas antibakteri. Peningkatan konsentrasi PEO pada emulsi Pickering memperkuat aktivitas antibakteri terhadap Staphylococcus aureus dan Escherichia coli, dengan film C2E40 menghasilkan zona hambat terbesar (22,00 mm dan 17,92 mm). Penambahan CNC juga menurunkan kadar air dan meningkatkan biodegradabilitas hingga 74,03% pada uji tanam tanah. Analisis SEM menunjukkan struktur lebih berpori seiring meningkatnya konsentrasi PEO. Secara keseluruhan, emulsi Pickering yang distabilkan CNC efektif meningkatkan distribusi dan pelepasan PEO, menghasilkan film bioplastik dengan sifat antibakteri dan biodegradabilitas yang lebih baik untuk aplikasi kemasan pangan.